A Case of Marginal Zone B-Cell Lymphoma in the Stomach Wall Resected for Gastric Cancer with Metastatic Lymph Node Involvement - Matsuno, Yoshihiro; Miyamoto, Masaki; Tamoto, Eiji; Kubota, Kanako; Nakakubo, Yoshihiro; Okushiba, Tomoo; Tobioka, Hirotoshi; Tanaka, Kimitaka; Kawamura, Takeshi (The Japanese Journal of Gastroenterological Surgery, 2011)
A case in which the natural course of extranodal marginal zone b-cell lymphoma is observed is rare, but previous reports support response to treatment, especially in slow tumor progression, as we report here. A 78-year-old man diagnosed with reactive lymphadenopathy in cervical lymph node biopsy was referred for surgery for gastric cancer found in gastric polyp biopsy. Preoperative examination showed enlarged neck, mediastinum, and paraaortic lymph nodes treated by total gastrectomy when cervical lymph node biopsy showed no gastric cancer metastasis. The resected specimen showed atypical lymphocyte invasion under tumors subsequently diagnosed immunohistochemically as marginal zone B-cell lymphoma. Similar cervical and paraaortic lymph node observation led to a diagnosis of gastric extranodal marginal zone b-cell lymphoma with metastatic lymph node involvement. Four outpatient courses of rituximab for lymphoma reduced enlarged mediastinal lymph nodes in one year. No recurrence has been seen in the 2 years since.